Growth stock investing advanced analysis : what you need to know - Domash, Harry (FT Press Delivers, 2011)
If you liked this Short, you might also like Fire Your Stock Analyst!: Analyzing Stocks On Your Own, 2nd Edition (9780137010233) by Harry Domash. Available in print and digital formats. How to pick market leaders that will earn the lion's share of industry profits! It pays to bet on an industry's strongest player. Don't believe me? Just check the profits Google shareholders have enjoyed compared to those who bet on Yahoo. Same for Intel versus AMD or Toyota versus GM or Ford. Spotting the industry leader is easy. Simply checking profit margins and revenue growth might tell you all you need to know.